Antimicrobial Properties of Amniotic and Chorionic Membranes: A Comparative Study of Two Human Fetal Sacs - M Zare-Bidaki; S Sadrinia; S Erfani; E Afkar; N Ghanbarzade (JRI, 2017)
Background: There is evidence of antibacterial properties of human chorioamniotic layer. However, the distinctive contribution of its individual parts, amniotic and chorionic membranes, to these effects is still unknown. The aim of present study was comparison of the antibacterial effects between amniotic and chorionic membranes. Methods: Chorioamniotic layer was removed from placenta belonging to 43 healthy mothers whose infants were delivered by caesarean section. Their amniotic and chorionic fetal tissues were manually peeled in sterile conditions. The antibacterial effects of all membrane samples were evaluated on 8 standard strains of bacterial collection using disk diffusion method on bacteriologic media. Results of bacterial growth inhibition in the presence of amniotic or chorionic membranes were measured and recorded as median±IQR. For data analysis and statistical comparison of samples, Kruskal-Wallis and Mann-Whitney U-test were applied using SPSS (v. 18). Results: Amniotic and chorionic membranes significantly showed different level of growth inhibitory effects on 8 bacterial strains including seven pathogens: E. coli, Bacillus cereus, Klebsiella pneumonia, Streptococcus pyogenes, Pseudomonas aeruginosa, Staphylococcus aureus, Shigella flexneri and one probiotic: Lactobacillus plantarum (p=0.018 and p<0.001, respectively). The number of bacterial growth inhibition zones around chorionic membranes was more than of what found around amniotic membranes. Conclusion: The superiority of antibacterial effects of the chorionic membrane compared with the amniotic membrane can represent the key role of maternal part in placenta in protecting the fetus against possible infections. The antimicrobial effect of amniotic and chorionic membranes is significantly different on various bacteria.